2019
DOI: 10.1371/journal.pgen.1008029
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular communication is required for trap formation in the nematode-trapping fungus Duddingtonia flagrans

Abstract: Nematode-trapping fungi (NTF) are a large and diverse group of fungi, which may switch from a saprotrophic to a predatory lifestyle if nematodes are present. Different fungi have developed different trapping devices, ranging from adhesive cells to constricting rings. After trapping, fungal hyphae penetrate the worm, secrete lytic enzymes and form a hyphal network inside the body. We sequenced the genome of Duddingtonia flagrans , a biotechnologically important NTF used to control nematod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 75 publications
3
79
0
2
Order By: Relevance
“…Specifically, NTF in response to the lifestyle switch enrich the production of thousands of metabolites, containing hundreds of structural families, as revealed by molecular networking. Our results and previous studies have collectively shown that the lifestyle switching of NTF is accompanied by physiological changes in transcriptome [7,8], proteome [7], and metabolome. Furthermore, such changes in the metabolome exhibit species-specificity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Specifically, NTF in response to the lifestyle switch enrich the production of thousands of metabolites, containing hundreds of structural families, as revealed by molecular networking. Our results and previous studies have collectively shown that the lifestyle switching of NTF is accompanied by physiological changes in transcriptome [7,8], proteome [7], and metabolome. Furthermore, such changes in the metabolome exhibit species-specificity.…”
Section: Discussionsupporting
confidence: 85%
“…The underlying physiochemical processes in developing the trapping devices are of great interest in biological research. Studies on genomic, transcriptomic, and proteomic aspects have collectively shown that the trap formation is associated with the upregulation of multiple signal transduction pathways, biosynthesis of adhesive proteins [7], intercellular communication [8], and nitrate assimilation [9]. On the other hand, little is known about the metabolome of NTF.…”
Section: Introductionmentioning
confidence: 99%
“…However, only recently have the molecular mechanisms underlying the singular biology of these specialized predators began to be uncovered. For example, a recent work has generated a strain lacking the signaling scaffold protein Soft and shown that cell-cell fusion is required for ring closure in Duddingtonia flagrans (41). In A. oligospora , ATCC24927-background trapping-deficient mutants have been isolated: adhesin protein Mad1 (42), autophagy protein Atg8 (43), mitogen-activated protein kinase Slt2 (44), pH sensor PalH (45), NADPH oxidase NoxA (46), low-affinity calcium uptake system proteins Fig1 and Fig2 (47), Rab GTPase Rab7A (48), actin-associated protein Crn1 (49), Woronin body component Hex1 (50), malate synthase Mls (51), glycogen phosphorylase Gph1 (52), transcription factors VelB (53) and StuA (54), and microRNA processing protein Qde2 (55), to which we add the G-protein ÎČ subunit Gpb1.…”
Section: Resultsmentioning
confidence: 99%
“…A few limitations of the use of D. flagrans include the necessity of cell-cell signaling in trap formation and constriction that requires hyphal fusion and a significant mycelial growth to achieve a switch from saprotrophic to zootrophic nutrition intake (Youssar et al 2019). This denotes a requirement of a certain threshold chlamydospore administration to cause sufficient growth for this transformation.…”
Section: Introductionmentioning
confidence: 99%